PSYCHOLOGICAL INFLUENCE OF POSITIVE UTILITY OF TRAVEL TIME TO TRAVEL BEHAVIOUR - Yosritzal, Yosritzal (FSTPT Indonesia, 2015)
There is increasing interest in understanding travel behaviour to predict the effect of a policy into the shape of transportation system. However, less attention has been given to the psychological aspect of the system that leads to travel behaviour changing. This paper overview a comprehensive research that combined psychological related research area into transportation especially travel behaviour. Specifically, this paper overview several studies on the psychological aspect of travel time with respect to the positive utility of travel time in data collection and analysis. There are three aspects of the effects discussed in this paper such as perception of time, attitudes, and value of time. The integration of the psychological research methods into transportation offers a deep understanding of travel behaviour at individual as well as aggregate level.